Emulsifier Dari Minyak Pliek U Dengan Reaksi Gliserolisis Menggunakan NButanol Sebagai Co-Solvent Dan Katalis MgO - Maulana, Teuku Ryan; Faridah, Faridah; Salmyah, Salmyah (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
Emulsifiers or emulsifying agents are one of the oleochemical products that have high economic value. One of the alternative ingredients that can be used as emulsifiers is Aceh palm oil (pliek u oil). In this study n-Butanol solvent is used which can increase the solubility of oil in glycerol so that the glycerolysis reaction can be carried out at low temperatures. This study aims to determine the effect of temperature and solvent ratio on the emulsifier produced. The catalyst used in the reaction is MgO (4% of oil weight), where the test variables used are reaction temperature (70, 80, 90, and 100◦C), 2 hours contact time, and the ratio of n-butanol to oil ( 1: 1, 1: 2, 1: 3 and 1: 4 v / v). The analysis was carried out in the form of an analysis of decreased levels of free fatty acids (ALB) by acid-base titration and Hydrophilic Lipophilic Balance (HLB) analysis to determine the type of emulsifier produced. The results showed that the greatest decrease in free fatty acid levels was found in the solvent to oil ratio of 1: 4 (v / v), and the temperature of 100◦C was 91.26%. The resulting HLB value of 19.68 is categorized into oil in water (o / w). The results obtained from this study indicate that pliek oil can be used as raw material for making emulsifiers using n-Butanol solvent and MgO catalyst.